Naimaecosync as a Waste Management Aggregator in Supporting Extended Producer Responsibility for Industries in Indonesia - Dewi, Mutia Rahmi; Islamy, Imam Teguh; Apridal, Fauzi Isyrin; Sy, Yulia Jihan; Atma, Yori Adi; Vadreas, Andrew Kurniawan (Formosa Journal of Sustainable Research, 2025)
Extended Producer Responsibility (EPR) is a program that holds industries accountable for their products' environmental impact throughout their lifecycle. To guide EPR implementation, Indonesia's Ministry of Environment and Forestry issued Regulation P.75/2019 on waste reduction by producers. One key government initiative is optimizing partnerships for post-consumer packaging waste collection through Waste Banks, TPST3R, Recycling Centers, and digital platforms. This research introduces NaimaEcoSync, a platform designed to streamline waste take-back by integrating waste management data and mapping reports for industries. Developed using the Scrum methodology, NaimaEcoSync achieved a usability score of 96.07%. The platform contributes to industry sustainability by reducing waste and supporting EPR implementation in Indonesia